Polyphenolic Contents and Antioxidant Properties of Different Grape (V. vinifera, V. labrusca, and V. hybrid) Cultivars - Nile, Shivraj Hariram (Hindawi Publishing Corporation, 2013)
The polyphenolic contents and the antioxidant activity of the skins and pulps of different grape cultivars were estimated using HPLC and DPPH antioxidant assay, respectively. The phenolics and flavonoids identified were quercetin, kaempferol, caffeic acid, p-coumaric acid, cinnamic acid, and (−)-epicatechin. The total phenolic contents were found to be the highest in the grape skin of Flouxa (>400 mg/100 g), followed by Campbell Early and Tamnara (>300 mg/100 g), and then by Red Globe and Ruby Seedless (>250 mg/100 g), and the total phenolic content was the lowest in Italia and Delaware (<60 mg/100 g). The antioxidant activities of the grape extracts varied from 12.5% (Ruby Seedless) to 60.2% (Hongiseul) for skins, whereas the antioxidant activities of the grape extracts varied from 35.4% (Campbell Early) to 84.5% (Hongiseul) for pulps. The grape pulps have stronger antioxidant activities than those of the grape skins. Our results suggest that the phenolic and flavonoid contents in extracts of grape skins and pulps showed statistically significant correlations with the free radical scavenging activity.